Electronic Structure, Bonding, and Stability of Boron Subphthalocyanine Halides and Pseudohalides. Issue 4 (10th February 2022) - Hildebrand, Mariana; Holst, Devon; Bender, Timothy; Kronik, Leeor
Abstract: Halides and pseudohalides of boron subphthalocyanine (BsubPc) are promising candidates for efficient yet stable organic photovoltaics. Here, the electronic structure of such molecules, obtained using density functional theory, is considered. Based on the calculations, it is found that the tetrameric boron bond is stabilized by an inductive effect at the axial substituent and by conjugative effects across the ring system. It is further found that stability is dictated mostly by the axial moiety, such that Br‐BsubPc is the most fitting precursor structure for further synthesis steps, whereas F‐BsubPc is the most suitable candidate for long‐term device performance. H‐BsubPc is examined as a new BsubPc derivative, and found to be too volatile for long term device performance. Finally, it is shown that peripheral substitution dictates the position of frontier orbitals, thereby allowing for essentially separate optimization of material properties and material stability. Abstract : Halides and pseudohalides of boron subphthalocyanine are promising for organic photovoltaics. Here, their electronic structure is computed. The tetrameric boron bond is found to be stabilized by an inductive effect at the axial substituent and conjugative effects across the ring system. Stability and frontier orbital positions are found to be dictated mostly by the axial moiety and peripheral substitution, respectively.